Spearcon Sequences for Monitoring Multiple Patients: Laboratory Investigation Comparing Two Auditory Display Designs. (March 2019) - Li, Simon Y. W.; Tse, Man-Kei; Brecknell, Birgit; Sanderson, Penelope M.
Objective: The aim was to compare the effectiveness of two auditory displays, implemented with spearcons (time-compressed speech), for monitoring multiple patients. Background: Sequences of sounds can convey information about patients' vital signs, such as oxygen saturation (SpO2 ) and heart rate (HR). We tested whether participants could monitor five patients using spearcon-based sound sequences. Method: A 2 × 3 within-subjects design was used. The first factor was interface, with two levels: the ALL interface used spearcons to convey vital signs for all five patients, whereas the ABN (abnormal) interface represented patients who had normal vital signs with a low-pitched single-tone sound and patients who had at least one abnormal vital sign with spearcons. The second factor was the number of patients who had at least one abnormal vital sign: there were one, two, or three such patients in each monitoring sequence. Participants were 40 nonclinicians. Results: Participants identified abnormal patients' SpO2 and HR levels and located abnormal patients in the sound sequence more accurately with the ABN interface than the ALL interface. Accuracy declined as the number of abnormal patients increased. Participants associated ABN with easier identification of vital signs, resulting in higher ratings of confidence and pleasantness compared with ALL. Conclusion: Sequences of spearcons may support effective eyes-free monitoring of multiple patients. Application: Sequences of spearcons may be useful in monitoring multiple patients and the underlying design principles may extend to monitoring in other domains such as industrial process control or control of multiple autonomous vehicles.